1984
DOI: 10.1111/j.1532-5415.1984.tb02040.x
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Consultation: A Functional Approach

Abstract: Eighty-one geriatric consultations conducted on behalf of 71 patients (mean patient age 78 years, range 59-99; M34 , F37 ) at San Francisco General Hospital were analyzed. Seventy-nine per cent of requests were for medical or psychiatric evaluation; 19 per cent social; and 3 per cent rehabilitation. The authors made 50 new diagnoses, many of which identified conditions that adversely affected patients' functional levels, including cardiovascular disorders (8), medication effects (8), malnutrition (7), misdiagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Although various geriatric consultative programs recently have been described, the efficacy of geriatric assessment in such a setting has yet to be demonstrated conclusively 15 – 19 . Differences in compliance due to the nature of the consultant (individual v team), length and/or form of the consultation, the patient population served, and the nature of the initial request from the primary care provider are but a few of the variables that must be considered in evaluating individual reports.…”
Section: Discussionmentioning
confidence: 99%
“…Although various geriatric consultative programs recently have been described, the efficacy of geriatric assessment in such a setting has yet to be demonstrated conclusively 15 – 19 . Differences in compliance due to the nature of the consultant (individual v team), length and/or form of the consultation, the patient population served, and the nature of the initial request from the primary care provider are but a few of the variables that must be considered in evaluating individual reports.…”
Section: Discussionmentioning
confidence: 99%
“…For hospital‐based GEM units, the length of index hospitalization is affected by the length of the assessment itself. Thus, some programs prolong initial length‐of‐stay, 44–46 but others reduce initial stay 26,31,36,39,47 . Studies following patients for at least 1 year, however, usually showed overall reduction in use of acute‐care hospital services, even in those programs with initially prolonged hospital stays 17,20,24,29 …”
Section: Geriatric Evaluation and Management Programs: Documented Benmentioning
confidence: 99%
“…However, several descriptive studies have attributed positive outcomes to geriatric consultations requested on the basis of such intuitive impressions. The team described by Lichtenstein and Winograd 34 received consultation requests primarily from internal medicine, family medicine, surgery, and surgical subspecialties. Focusing on social and medical conditions that interfered with independent living, these geriatricians identified 50 new diagnoses.…”
Section: Strategies For Targeting Geriatric Servicesmentioning
confidence: 99%
“…Focusing on social and medical conditions that interfered with independent living, these geriatricians identified 50 new diagnoses. After consultation, 51% of patients who were slated for nursing home placement were re‐routed to lower levels of care 34 . Duthie and Gambert 35 also described a consult team that functioned by request based on implicit, intuitive criteria.…”
Section: Strategies For Targeting Geriatric Servicesmentioning
confidence: 99%